Cambarus fetzneri sp. nov., a new species of burrowing crayfish (Decapoda: Cambaridae) from the Allegheny Mountains of Virginia and West Virginia, USA - Loughman, Zachary J.; Welsh, Stuart A.; Thoma, Roger F. (Zootaxa, 2019)
The disjunct distribution of Cambarus monongalensis has led to speculation about its taxonomic status. An Appalachian Plateau population occurs in northern and central West Virginia and Southwestern Pennsylvania, and a mountain population occurs in the Allegheny Mountains and Ridge and Valley physiographic provinces of the Virginias. Herein we describe the mountain population as Cambarus fetzneri sp. nov. The two species differ genetically and morphologically, and have different color patterns. Specifically, C. fetzneri sp. nov. chelae lack extensive red coloration on the distal end of the propodus and dactyl, possess rostral margins that lack any red coloration, compared to C. monongalensis, which has extensive red coloration on the dactyl and propodus, as well as red rostral margins. Morphologically, the rostrum of C. fetzneri sp. nov. is shorter and wider than that of C. monongalensis. Also, adult C. fetzneri sp. nov. are considerably smaller in body size than those of C. monongalensis.